2019
DOI: 10.1007/s11116-019-10052-4
|View full text |Cite
|
Sign up to set email alerts
|

The German value of time and value of reliability study: the survey work

Abstract: In 2012 Germany’s Federal Ministry of Transport and Digital Infrastructure (BMVI) initiated several projects in preparation of the new Federal Transport Infrastructure Plan (BVWP) 2030. This included an update of the general methodology and in particular of its cost–benefit analysis which is used to evaluate the effects of hundreds of German infrastructure projects under study. As part of the work the first official values of time (VOT) and values of reliability (VOR) for personal and business travel for Germa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“… Wardman et al, 2016 ). Recent developments in this field are found in the VOT studies for Great Britain (see Batley et al, 2017 , Department for Transport, 2015 ), the Netherlands (see Significance et al, 2012 ), Scandinavian countries (see Börjesson and Eliasson, 2012 , Fosgerau et al, 2007 , Ramjerdi et al, 2010 ), Germany (see Axhausen et al, 2014 , Dubernet and Axhausen, 2019 ), and Switzerland (see Axhausen et al, 2004 , Axhausen et al, 2008 , Fröhlich et al, 2012 , Weis et al, 2012 , Dubernet et al, 2018 ). SP studies allow cost-benefit analyses for infrastructure projects, where travel time savings often make up the largest share of gains ( Mackie et al, 2001 ; for similar results in Switzerland and Germany see ARE, 2016a , ARE, 2016b , BMVI, 2016 ).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“… Wardman et al, 2016 ). Recent developments in this field are found in the VOT studies for Great Britain (see Batley et al, 2017 , Department for Transport, 2015 ), the Netherlands (see Significance et al, 2012 ), Scandinavian countries (see Börjesson and Eliasson, 2012 , Fosgerau et al, 2007 , Ramjerdi et al, 2010 ), Germany (see Axhausen et al, 2014 , Dubernet and Axhausen, 2019 ), and Switzerland (see Axhausen et al, 2004 , Axhausen et al, 2008 , Fröhlich et al, 2012 , Weis et al, 2012 , Dubernet et al, 2018 ). SP studies allow cost-benefit analyses for infrastructure projects, where travel time savings often make up the largest share of gains ( Mackie et al, 2001 ; for similar results in Switzerland and Germany see ARE, 2016a , ARE, 2016b , BMVI, 2016 ).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Lindhjem and Navrud (2011a) believe some of this effect may be due to more honest responses and less social desirability bias in internet panel surveys giving lower willingness to pay responses.6 Note that 'intercept' could imply either that respondents answer the survey right away on the location where they are recruited (on-site) or that they leave their contact info or receive a link to the questionnaire and answer it later.7 In the 2012 German study, the non-business respondents who were recruited by phone were asked if they wanted to complete the survey on-line. However, only 5.6 percent of the respondents choose to do so which does not allow for a sensible test regarding the effect of interview type(Dubernet and Axhausen 2020). In the 2014 UK study, no results on the effect of source of recruitment or interview type are reported(Batley et al 2017).…”
mentioning
confidence: 99%
“…The interest on the value of time is longstanding—with Becker ( 1965 ), Beesley ( 1965 ), and DeSerpa ( 1971 ) credited as pioneers of the microeconomic modelling of time allocation (Dubernet and Axhausen 2020 ). Current practice in the transportation literature heavily relies on stated preferences gathered through discrete choice experiments (DCE) (Beck et al.…”
Section: Related Literaturementioning
confidence: 99%